Factors influencing financial planning retirement amongst employees in the private sector in East Coast Malaysia: literature review and research agenda - Hasnah, Haron; Nur Nadiah Salihah, Mat Razali; Fazeeda, Mohamad (KnE Social Sciences, 2019)
Gerontology is the main concern about the social, psychology, social, cognitive and biological aspects of aging. This paper focuses on the aging population in Malaysia as there is an increase in the number of 60 years old in the country. Malaysia will be labeled “old status country” in the year 2035 according to the Department of Statistics Report (2016). There is a lack of awareness to save for old age amongst Malaysians. Malaysians tend to procrastinate in this issue thinking that their retirement is still a long way off. This paper will identify the Malaysians behavior in making forecasting planning for their retirement. It comprises the predictors of retirement plans based on the attitude for savings, level of consumption, investing wisely, and financing consumption during the pre-retirement period. This study will conduct using the quantitative approach focusing on the employees in the private sector with at least ten years left of service before achieving the retirement age. The study will use regression analysis to analyses the data. It is hoped that this finding will confirm the relevance of planning constructs and enhance retirement savings behavior, following establishes a need to improve levels of financial knowledge in society.